Compositional mapping of Vesta quadrangle V24 - Tosi, F.; De sanctis, Maria Cristina; Nathues, A.; Ammannito, E.; Frigen, A.; Zambon, A.; Palomba, E.; Capaccioni, F.; Yingst, A.; Jaumann, Ralf; Stephan, Katrin; Pieters, C.; et al. (2012)
The Dawn spacecraft [1] entered orbit around Vesta in mid-July 2011. Since then, the Visible and InfraRed Imaging Spectrometer (VIR) [2] acquired hyperspectral images of Vesta’s surface in the overall wavelength range from 0.25 to 5.1 μm. During the Approach and Survey mission phases (23 July through 29 August 2011), VIR obtained resolved images of Vesta with spatial resolutions between 1.31 km and 0.68 km/pix. More than 65% of the surface, from the South Pole up to ∼40°N, was observed under different illumination conditions and local solar elevations. Based on this datasets, a series of four quadrangle maps following the scheme in [3] are being produced showing the results derived from the spectroscopic analysis of VIR data. In this work we present the results of the spectroscopic analysis achieved for the quadrangle V-24, which covers Vesta’s southern polar region 55°S - 90°S and longitude 0° - 360°.